2015
DOI: 10.1093/bioinformatics/btv631
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference with historical data-based informative priors improves detection of differentially expressed genes

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…For example, in pediatric studies Bayesian methods are typically used to explicitly borrow information from other adult trials or previous pediatric studies . See also Viele et al, Ibrahim et al, Takeda et al, and Li et al for a more general overview of benefits resulting from borrowing historical information in the analysis of the current trial. On the other hand, the use of highly informative priors in case of low sample size may lead to a domination of the prior, rather than the data, on the posterior inferences.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in pediatric studies Bayesian methods are typically used to explicitly borrow information from other adult trials or previous pediatric studies . See also Viele et al, Ibrahim et al, Takeda et al, and Li et al for a more general overview of benefits resulting from borrowing historical information in the analysis of the current trial. On the other hand, the use of highly informative priors in case of low sample size may lead to a domination of the prior, rather than the data, on the posterior inferences.…”
Section: Methodsmentioning
confidence: 99%
“…For microarray data analysis, [ 21 , 22 ] argued that borrowing information across all genes might lead to over-correction. A better approach is to apply gene-specific or group-specific prior based on historic data to share information only across genes with similar variances.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, the novel IPBT approach has shown to improve DE gene detection by using historical data (Li et al 2015). Although it has been shown that IPBT is reasonably robust when the historical data is rather noisy, its performance is somewhat sensitive to the quality of the corresponding historical data since IPBT uses historical SD directly.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the diverse biological features of developmental genes, housekeeping genes, response genes are reflected in their expression profiles measured from many different conditions. As shown in the Figure 1 of Li et al (2015), there are substantial differences in terms of means and variances from gene to gene. Given heterogeneity in high-throughput genomics data, it is counter-productive for a highly and stably expressed housekeeping gene to borrow information from developmental genes with a bimodal expression pattern across experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation